1993
DOI: 10.1007/bf00180071
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of glomerular matrix proteins in the pathogenesis of diabetic nephropathy

Abstract: Diabetic late complications are characterized by morphological and biochemical alterations of the extracellular matrix. In particular, longstanding diabetes causes quantitative and qualitative changes in basement membrane structure of retinal and renal capilleries. Immunohistochemical investigations of diabetic kidneys with diffuse glomerulosclerosis show increased collagen type IV deposition in the mesangial matrix and decreased heparan sulfate proteoglycan content in the mesangial matrix and glomerular basem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The association between glomerular sclerosis and proteinuria suggests that altered ECM composition may contribute to the loss of permselectivity (7,9,14). Alternatively, the glomerular events that ultimately result in proteinuria and loss of GFR may also initiate sclerosis as an independent but concurrent event.…”
mentioning
confidence: 93%
“…The association between glomerular sclerosis and proteinuria suggests that altered ECM composition may contribute to the loss of permselectivity (7,9,14). Alternatively, the glomerular events that ultimately result in proteinuria and loss of GFR may also initiate sclerosis as an independent but concurrent event.…”
mentioning
confidence: 93%
“…For instance, hyperglycemia increases diacylglycerol levels and activates protein kinase C activity in the aorta of streptozotocin (STZ) 1 -induced diabetic rats (5) and dogs (6). Thickening of the basement membranes in renal glomeruli and peripheral capillaries has been observed in STZ-induced diabetic rats (7) and diabetic patients (4). Hyperlipidemia is a feature of drug-induced diabetes in rats (8) and rabbits (9, 10), as well as poorly controlled diabetes in humans (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro data have indicated that thrombin, through the activation of PAR-1, contributes to the pathology of acute renal injury and that APC plays a renoprotective role, possibly in part through the activation of the same receptor on kidney cells (Xu et al, 1995; Gupta et al, 2007, 2009; Isermann et al, 2007). These studies have used primary or immortalized proximal tubule epithelial (HK-2) cells as in vitro models to conclude that thrombin can initiate proinflammatory responses in the kidney through the stimulation of TGF-β and subsequent induction of ECM proteins (MacKay et al, 1989; Olgemoller and Schleicher, 1993; Ryan et al, 1994; Laping et al, 1997; Grandaliano et al, 2000; Shirato et al, 2003; Vesey et al, 2005; Du et al, 2010). The accumulation of ECM molecules is one common pathological feature of glomerular and tubular diseases observed in end-stage renal failure caused by severe sepsis and diabetic nephropathy (Wan et al, 2003; Bonventre and Zuk, 2004; Molitoris and Sutton, 2004).…”
mentioning
confidence: 99%